Factors Affecting House Purchasing - A Case Study In Bukit Mertajam - Ooi, Seong Kang (Pusat Pengajian Ilmu Kemanusiaan, 1982)
The study revealed that the increase in the number of housing units was very rapid, especially from 1975. In addition the housing expansion were directed towards the outskirts of the town. This was particularly true around the Terminal region of the Penang Bridge where large tract of extensive land were converted into housing estates. These areas were developed almost at the same time as each other.